Contribution of flavonoids to the antioxidant properties of common and tartary buckwheat. (March 2016) - Lee, Lan-Sook; Choi, Eun-Ji; Kim, Chang-Hee; Sung, Jung-Min; Kim, Young-Boong; Seo, Dong-Ho; Choi, Hyun-Wook; Choi, Yun-Sang; Kum, Jun-Seok; Park, Jong-Dae
Abstract: The objective of this study was to characterize the flavonoid compounds found in the different grain parts of common and tartary buckwheat, and to determine the contribution of these flavonoids to the antioxidant properties of buckwheat. Eight flavonoid compounds were quantified and their antioxidant activity determined by FRAP, DPPH, and ABTS assays. Of the flavonoid compounds identified rutin was the most abundant, particularly in tartary buckwheat, in which it comprised approximately 90% of total flavonoid content. Flavan-3-ols were detected in common but not tartary buckwheat, and quercetin was detected only in tartary buckwheat. Flavonoid content—in particular, levels of rutin, orientin, and/or epicatechin gallate—was found to influence the total antioxidant activity of buckwheat. Results from this study indicate that antioxidant activity is not only closely associated with flavonoid content, but that different flavonoids contribute differently to the total antioxidant activity of common and tartary buckwheat. Highlights: Catechin and epicatechin gallate (ECg) were found only in common buckwheat. Quercetin was observed only in tartary buckwheat. The highest antioxidant activity was observed in tartary groats. ECg was the main contributor to antioxidant activity of common buckwheat hull. Rutin, orientin, and/or ECg contents were highly correlated with the antioxidant activity.